2020
DOI: 10.6007/ijarbss/v10-i6/7329
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Influence of English Language on Islamic Identity and Value of Students Enrolled in an Islamic-Oriented Human Resource Education Programme

Abstract: In Malaysia, English has been heavily emphasized in education with the main goal of proficiency in both Malay and English for all. Like any other language, English is associated with the culture of its native speakers. Hence, it may also be perceived as the carrier of Judeo-Christian values and Western cultures. This may lead to the perception that learning English is a threat to Islamic identity and values, causing rejection. Therefore, with the increasing demand for capable English speakers in the Malaysian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Thus, the active introduction of content and language integrated learning into the educational process can increase the level of English proficiency among students. Unlike most studies (Hu et al, 2021;Jailani et al, 2020) that have examined the effect of integrated English teaching with specialised disciplines, studying Islamic culture and religion in conjunction with English can have a positive synergistic effect (Hypothesis 5).…”
Section: Volume 38mentioning
confidence: 80%
See 1 more Smart Citation
“…Thus, the active introduction of content and language integrated learning into the educational process can increase the level of English proficiency among students. Unlike most studies (Hu et al, 2021;Jailani et al, 2020) that have examined the effect of integrated English teaching with specialised disciplines, studying Islamic culture and religion in conjunction with English can have a positive synergistic effect (Hypothesis 5).…”
Section: Volume 38mentioning
confidence: 80%
“…moral hygiene) recommends avoiding elements that have a detrimental effect on the Muslim identity, morality, and attitude (Dashti et al, 2021). Therefore, some students use English only in class or for homework, completely eliminating the possibility of communication outside the classroom as an additional route for the development of their English skills (Dashti et al, 2021;Jailani et al, 2020). Thus, we set Hypothesis 1: Muslim communities have a collective responsibility to study foreign languages.…”
Section: Volume 38mentioning
confidence: 99%
“…There might be concern over students of tahfiz institution rejecting the language due its native speakers' background, values and religion. Nevertheless, a study by Jailani et al (2020), found that the respondents who enrolled in islamic-oriented education program in Malaysia still had high acceptance of the language and significantly disagreed that it had negative effects on their religious identity and islamic values.…”
Section: Malaysian Tahfiz Education Systemmentioning
confidence: 99%